Hurricane Jim Crow : how the Great Sea Island Storm of 1893 shaped the Lowcountry South - Grego, Caroline (Book collections on Project MUSE., 2022)
"On an August night in 1893, the deadliest hurricane in South Carolina history struck the Lowcountry, killing thousands-almost all African American. But the devastating storm is only the beginning of this story. The hurricane's long effects intermingled with ongoing processes of economic downturn, racial oppression, resistance, and environmental change. In the Lowcountry, the political, economic, and social conditions of Jim Crow were inextricable from its environmental dimensions. This narrative history of a monumental disaster and its aftermath uncovers how Black workers and politicians, white landowners and former enslavers, northern interlocutors and humanitarians all met on the flooded ground of the coast and fought to realize very different visions for the region's future"--